Animals with Coxiella burnetii Infection Demonstrate a Western Immunoblot Profile of Chronic Q Fever in Humans - TJ Marrie; Linda Yates (Canadian Journal of Infectious Diseases)
Western immunoblotting was used to compare the immune response to Coxiella burnetii phase I and phase II antigens of humans with acute and chronic Q fever with that of infected cats, rabbits, cows and raccoons. The cats, rabbits, cows and raccoons had an immunoblot profile similar to that of the human with chronic Q fever.